2023
DOI: 10.7554/elife.80670
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of cell types in the squid Loligo vulgaris

Abstract: Cephalopods are set apart from other mollusks by their advanced behavioral abilities and by the complexity of their nervous systems. Because of the great evolutionary distance that separates vertebrates from cephalopods, it is evident that higher cognitive features have evolved separately in these clades despite the similarities that they share. Alongside their complex behavioral abilities, cephalopods have evolved specialized cells and tissues, such as the chromatophores for camouflage or suckers to grasp pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 105 publications
0
13
0
Order By: Relevance
“…SoxB1-positive ectodermal regions in cephalopods are accompanied by epithelial thickenings, which are hypothesized to give rise to neuronal precursors of the centralized brain (Deryckere et al, 2021). Single-cell transcriptomic data suggest the presence of SoxB1 both in neural migrative precursors together with the expression of Ascl and in some maturing neurons (Duruz et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SoxB1-positive ectodermal regions in cephalopods are accompanied by epithelial thickenings, which are hypothesized to give rise to neuronal precursors of the centralized brain (Deryckere et al, 2021). Single-cell transcriptomic data suggest the presence of SoxB1 both in neural migrative precursors together with the expression of Ascl and in some maturing neurons (Duruz et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In Lottia goshmanii , another representative of the Patellogastropoda, SoxB1 expression has been described in compact zones on the ventral posterior surface of the trochophore (Tan et al, 2022). The role of SoxB1 and SoxB2 in neurogenesis has been most thoroughly studied in cephalopods, Octopus vulgaris and Sepia officinalis (Buresi et al, 2016; Focareta and Cole, 2016; Deryckere et al, 2021; Duruz et al, 2023). The authors of all these papers mention that SoxB1 exhibits broad ectodermal expression at early neurogenic stages and further in development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurons of the medulla have processes within superficial layers of the optic lobe as well as locally within the medulla, and many project axons out from the optic lobe to downstream visual areas. Recent transcriptomic studies have further revealed a rich diversity of cell types within the optic lobe, as well as extensive sub-laminar organization (Songco-Casey et al 2022; Styfhals et al 2022; Gavriouchkina et al, 2022; Duruz et al 2023).…”
Section: Introductionmentioning
confidence: 99%